Central apnoeas and ticagrelor-related dyspnoea in patients with acute coronary syndrome. Issue 3 (15th July 2020) - Giannoni, Alberto; Borrelli, Chiara; Gentile, Francesco; Mirizzi, Gianluca; Coceani, Michele; Paradossi, Umberto; Vergaro, Giuseppe; Bramanti, Francesca; Iudice, Giovanni; Emdin, Michele; Passino, Claudio
Abstract: Aims: Dyspnoea often occurs in patients with acute coronary syndrome (ACS) treated with ticagrelor compared with other anti-platelet agents and is a cause of drug discontinuation. We aimed to explore the contribution of central apnoeas (CA) and chemoreflex sensitization to ticagrelor-related dyspnoea in patients with ACS. Methods and results: Sixty consecutive patients with ACS, preserved left ventricular ejection fraction, and no history of obstructive sleep apnoea, treated either with ticagrelor 90 mg b.i.d. ( n = 30) or prasugrel 10 mg o.d. ( n = 30) were consecutively enrolled. One week after ACS, all patients underwent two-dimensional Doppler echocardiography, pulmonary static/dynamic testing, carbon monoxide diffusion capacity assessment, 24-h cardiorespiratory monitoring for hypopnoea–apnoea detection, and evaluation of the chemosensitivity to hypercapnia by rebreathing technique. No differences were found in baseline demographic and clinical characteristics, echocardiographic, and pulmonary data between the two groups. Patients on ticagrelor, when compared with those on prasugrel, reported more frequently dyspnoea (43.3% vs. 6.7%, P = 0.001; severe dyspnoea 23.3% vs. 0%, P = 0.005), and showed higher apnoea–hypopnoea index (AHI) and central apnoea index (CAI) during the day, the night and the entire 24-h period (all P < 0.001). Similarly, they showed a higher chemosensitivity to hypercapnia ( P = 0.001). Among patients treated with ticagrelor, those referring dyspnoea had the highest AHI, CAI, and chemosensitivity to hypercapnia (all P < 0.05). Conclusion: Central apnoeas are a likely mechanism of dyspnoea and should be screened for in patients treated with ticagrelor. A drug-related sensitization of the chemoreflex may be the cause of ventilatory instability and breathlessness in this setting.